Exploring AFL teachers’ experiences in teaching Arabic vocabulary: Reserch Article - Frida Akmalia (Indonesian Reseacher for Language Learning and Teaching, 2023)
The extent of one's vocabulary and the depth of one's knowledge of a term are two of the most important factors in one's command of the language. The focus of this study is on the vocabulary-teaching practices of Arabic as a Foreign Language (AFL) teachers. Narrative inquiry is used in this study to provide insight on the challenges faced by AFL teacher, the strategies, and the evaluations when seeking to instruct their students in Arabic vocabulary. Several AFL teachers use singing and role-play strategies to introduce students to Arabic vocabulary. Using a number of applications and google form media, teachers can administer puzzle games as a means of assessing their students' knowledge.